2022
DOI: 10.1177/10870547221085505
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Modular Segregation of White Matter Brain Networks in Attention Deficit Hyperactivity Disorder

Abstract: Objective: Despite studies reporting alterations in the brain networks of patients with ADHD, alterations in the modularity of white matter (WM) networks are still unclear. Method: Based on the results of module division by generalized Louvain algorithm, the modularity of ADHD was evaluated. The correlation between the modular changes of ADHD and its clinical characteristics was analyzed. Results: The participation coefficient and the connectivity between modules of ADHD increased, and the modularity coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 76 publications
2
10
0
Order By: Relevance
“…In addition, the striatum is thought to play an important role in ADHD symptomatology Cubillo et al, 2012). While the previous NBS studies shared some areas with our study, their findings focused on decreased segregation of the default and salience networks from other networks (Lin et al, 2018), and between areas encoding emotional and visual processing and the default mode network (He et al, 2022). Therefore, the results of the prior adult ADHD studies may represent different aspects of alterations in the brain network wiring.…”
Section: Network-based Statistics (Nbs)supporting
confidence: 51%
See 2 more Smart Citations
“…In addition, the striatum is thought to play an important role in ADHD symptomatology Cubillo et al, 2012). While the previous NBS studies shared some areas with our study, their findings focused on decreased segregation of the default and salience networks from other networks (Lin et al, 2018), and between areas encoding emotional and visual processing and the default mode network (He et al, 2022). Therefore, the results of the prior adult ADHD studies may represent different aspects of alterations in the brain network wiring.…”
Section: Network-based Statistics (Nbs)supporting
confidence: 51%
“…Although graph theory is becoming an increasingly common analytical approach in brain imaging, there are only few previously published structural MRI studies utilizing this approach in adults with ADHD and studying whole-brain topological features (He at al., 2022;Hearne et al, 2021;Sidlauskaite et al, 2015;Wang et al, 2021). While some previous studies have found global differences in adults with and without ADHD (He et al, 2022;Wang et al, 2021), others have come to a conclusion that ADHD related alterations are not seen in global topology (Hearne et al, 2021;Sidlauskaite et al, 2015). While the results of the present study bring more evidence to the latter, more studies are needed to demonstrate if there are more subtle subnetworks that characterize aberrant structural connectivity in adult ADHD.…”
Section: Graph-theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, so far only two studies of adult ADHD have utilized NBS together with DW-MRI. He and colleagues (2022) found increased connectivity in the ADHD group in relation to NT controls between several regions including subcortical structures such as amygdala, thalamus and putamen, and medial, frontal and orbital cortical regions. On the other hand, Hearne and colleagues (2021) found no significant networks differentiating adults with ADHD from NT controls.…”
Section: Introductionmentioning
confidence: 86%
“…Using the PC, neuroimaging research has suggested atypical modular segregation in patients with various psychiatric disorders. For instance, He et al found that participants with attention‐deficit/hyperactivity disorder had lower modular segregation of white matter networks (He et al, 2022). Notably, Ma et al reported reduced modular segregation in the FPN, SMN, visual, and subcortical modules across patients with schizophrenia, bipolar disorder, and major depressive disorder (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%